THU0299 Interpretation of 18F-Fluorodeoxyglucose Uptake by Arterial Grafts in Patients with Large Vessel Vasculitis – A Conundrum. (9th June 2015) - Youngstein, T.; Mukherjee, J.; Tombetti, E.; Humphreys, E.; Nash, J.; Andrews, J.; Mason, J.C.
Abstract : Background: 18 F-Fluorodeoxyglucose positron emission computerised tomography (FDG-PET-CT) is commonly used to aid the diagnosis of large vessel vasculitis (LVV). Its precise role and sensitivity during follow-up of LVV remains to be defined, and use is typically restricted to investigation of an unexplained acute phase response. We have encountered an additional limitation in LVV patients with synthetic arterial grafts, namely interpretation of FDG uptake confined to the graft. This is typically reported as vasculitic activity or infection, even in the absence of supportive clinical data. Objectives: To investigate non-specific uptake of FDG by synthetic arterial grafts in LVV. Methods: Twelve patients with FDG-uptake localised to arterial grafts were identified, 10 with LVV, and 2 with non-inflammatory aortopathy. The maximum standardised uptake values (SUV) for the grafts were quantified. The intensity of uptake by each graft and the native aorta was scored against constitutive hepatic uptake. Time after surgery, C-reactive protein, and infection screen results were obtained. Disease progression was estimated by magnetic resonance angiography (MRA). Results: Twelve patients (10 female, mean age 41.4 yrs, range 23-60) who had undergone graft surgery and FDG-PET scanning were identified, 8 with Takayasu arteritis (TA), 2 giant cell aortitis, 1 Marfan's syndrome and 1 non-inflammatory aortic wall degeneration (Table ). The index case (patient 1) presented with fatigue 2 years post-surgery. An FDG-PET-CT demonstrated increased FDG uptake specifically localised to the graft site, raising concerns regarding active LVV or graft infection. However, blood indices including leukocyte count and acute phase reactants were normal, and repeat blood cultures revealed no infection. Study of nine other LVV patients revealed directly comparable findings (Table ). The 2 patients with non-inflammatory disease also demonstrated significant uptake in aortic grafts, with no identifiable cause. The mean time post-surgery to first scan was 40 months (range 6-90). The mean maximum SUV of the grafts was (4.29±1.22). The uptake score in the grafts and native aorta relative to the liver were 2.83±0.39 versus 0.42±0.67 respectively (p<0.001). The CRP was not raised (mean ± SD 5.95±4.82, NR<10 mg/L), no infections were identified. Eight patients had repeat FDG-PET-CT scans with similar graft specific uptake identified. In 9 patients treatment was left unchanged. In 2 cases immunosuppression was increased and one received antibiotics, both without any change in FDG uptake. In those with LVV, immunosuppression has been subsequently weaned/withdrawn in all cases with no disease progression at 76.5 months (range 9-180). Conclusions: Although FDG-PET-CT scanning has proved useful for the diagnosis of active LVV, its role in the follow-up of patients on treatment remains undecided. FDG uptake confined to synthetic graft sites in LVV does not necessarily equate to infection or active vasculitis requiring treatment escalation. Uptake may represent a macrophage-driven foreign body reaction to the graft. Scans need to be interpreted cautiously and in conjunction with other clinical indices. Disclosure of Interest: None declared